MLL-rearranged B lymphoblastic leukemias selectively express the immunoregulatory carbohydrate-binding protein galectin-1 - Juszczynski, Przemyslaw (2010)
Leukemias with 11q23 translocations involving the Mixed Lineage Leukemia (MLL) gene exhibit unique clinical and biological features and have a poor prognosis. In a screen for molecular markers of MLL rearrangement, we identified the specific overexpression of an immunomodulatory lectin Galectin-1 (Gal1) in MLL-rearranged B lymphoblastic leukemias (B-ALL) compared to other MLL-germline ALLs. To assess the diagnostic utility of Gal1 expression in identifying MLL-rearranged B-ALLs, we performed Gal1 immunostaining on a large series of primary ALLs with known MLL status. All 11 MLL-rearranged B-ALLs had abundant Gal1 expression; in marked contrast, only 1 of 42 germline-MLL B-ALLs expressed Gal1. In addition, Gal1 was readily detected in diagnostic samples of MLL-rearranged B-ALLs by intracellular flow cytometry. Since deregulated gene expression in MLL-rearranged leukemias may be related to the altered histone methyltransferase activity of MLL fusion protein complex, we analyzed histone H3 lysine 79 (H3K79) dimethylation in the Gal1 promoter region using chromatin immunoprecipitation. Gal1 promoter H3K79diMe was ≈ 5 fold higher in a MLL-rearranged B-ALL cell line than in a B-ALL line without the MLL translocation. Furthermore, the Gal1 promoter H3K79 was significantly hypermethylated in primary MLL-rearranged B-ALLs compared to MLL-germline B-ALLs and normal pre-B cells, implicating this epigenetic modification as a mechanism for Gal1 overexpression in MLL B-ALL.